MENERAPKAN AJARAN PURGE SEBAGAI WUJUD DEMOKRASI - Michael, Tomy (Institut Hindu Dharma Negeri Denpasar, 2020)
The purpose of the research to find out if Purge is one way to reach democracy today? Research uses normative research with an orientation that is not sourced on conceptual attitudes that must be taken but also a combination of legislation that is a fundamental belief. The result is that when the state does not act decisively against any form of crime or violation of the law therein there are two possibilities, namely rebellion from the community and the release to the community to resolve properly. Purge's settlement is not contrary to democracy because Purge seeks to be a democracy more in the justice of society.Keywords: Democracy; law; Purge